ANALYSIS OF THE IMPACT OF RELIANCE JIO INFOCOMM LTD ON INDIAN ECONOMY: A CASE STUDY - Parvathy M. Madhavan , Abhijit Chirputkar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose of Study: Introduction of Reliance Jio was a breakthrough step in the Indian Telecom Sector because of predatory pricing which disrupted the existing telecom operators’ business. It resulted in a major market consolidation in the sector with almost fifteen operators exiting the market and resulting in only four major operators in the country. In the last three years, the internet subscriber base of the country has grown from 250 million to 550 million and R Jio plays a very important role in this rise. The investments in Reliance Jio from big enterprises around the world are also giving a boost to the economic growth of the country. Research gap: The academic literature has cases on Reliance Jio, however there are no cases on the impact of Reliance Jio and its subsidiaries on the economic and technological growth of the country. Objective: This study focuses on various ways in which Reliance Jio has helped in the growth of the Indian economy.